Orientasi Nilai Pelaku Musik Hardcore - Anto Sanjaya; Mochamad Widjanarko (Universitas Muria Kudus, 2010)
Human being is unique. No one is either physically or psychologically identical with others. Being different from others requires courage and is the choice in life. Selection of value orientation will make an individual being has a way and control of life as a form of value orientation which is believed and embraced. Hardcore music performer is one of many differences in value orientation adopted by men. A hardcore music performer certainly has a reason in choosing it as a a way of life.The objective of the research is to know and to understand the value orientation of the hardcore music performers in the Kudus Regency. The informants of the reasearch are the hardcore music performers located in Kudus Regency who are involved in Komunitas Kudus Hardcore Community (KDHC). Value orientation in the research is viewed by using motivational types of value which is proposed by Schwartz. Orientation value proposed by Schwartz consists of 10 types of values consisting of power, prestige, pleasure, stimulation, self direction, unity, virtue, tradition, compatibility and security.Based on the coding of interviews and observations conducted on the three informants shows that the hardcore music performers in Kudus Regency have value orientations that lead to the value of creativity and the other value that stands out is the value orientation led to the value of independence.